Prognostic Value of Metabolic Syndrome in Patients With Non-ST Elevated Myocardial Infarction Undergoing Percutaneous Coronary Intervention - Zhao, Li-Hong; Liu, Yin; Xiao, Jian-Yong; Wang, Ji-Xiang; Li, Xiao-Wei; Cui, Zhuang; Gao, Jing (Frontiers in Cardiovascular Medicine, 2022)
Objective We aim to investigate the prognostic effects of metabolic syndrome (MS) on patients with non-ST elevated myocardial infarction (NSTEMI) after percutaneous coronary intervention (PCI). Methods NSTEMI patients undergoing PCI were consecutively collected. According to the presence or absence of MS, they were divided into two groups, and followed up for 1 year. The endpoint was major adverse cardiovascular events (MACE), according all-cause death, unstable angina hospitalization, heart failure (HF) hospitalization, nonfatal recurrent myocardial infarction (MI), and target lesion revascularization. And Six subgroups were made according to gender, age, LVEF, GRACE score, hsTNT, and number of diseased vessels. Cox proportional hazard model was adopted to analyze the effect of MS on MACE in overall patients and in different subgroups. Results A total of 1295 patients were included in the current analysis and 660 (50.97%) of them had MS. 88 patients were lost to follow-up, the overall average follow-up was 315 days. MS was an independent risk factor for MACE (HR 1.714, CI 1.265-2.322, p=0.001), all-cause death, HF hospitalization and non-fatal recurrent MI. In MS component, BMI≥28kg/m2 was positively associated with MACE. Subgroup analysis indicated the prognostic value of MS was more striking for patients whose age>60, LVEF≤40%, GRACE>140, multivessel disease or hsTNT >0.1ng/ml. Conclusions MS was a robust adverse prognostic factor in patients diagnosed with NSTEMI, especially among those of older age and at higher ischemic risk. BMI≥28kg/m2 independently predicted the occurrence of MACE. Prognosis may be improved by controlling abdominal obesity.